2017
DOI: 10.1080/1343943x.2017.1355737
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soil exchangeable potassium content on cesium absorption and partitioning in buckwheat grown in a radioactive cesium-contaminated field

Abstract: The effect of soil exchangeable (plant-available) potassium (ExK) content on cesium (Cs) absorption and translocation in buckwheat was evaluated in a field contaminated with radioactive Cs (134 Cs and 137 Cs, RCs) in 2013. The RCs concentration in buckwheat was significantly positively correlated with the naturally occurring stable Cs (133 Cs, SCs) concentration, and was lower at higher soil ExK content. The RCs and SCs were actively absorbed by buckwheat until the flowering stage. The soil ExK content was sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…A decrease in grain RCs concentration with increasing soil ExK content was also observed in a field that had not been physically decontaminated (soil RCs concentration; <5000 Bq kg −1 ) (Kubo et al, 2015). Kubo et al (2017) demonstrated that higher soil ExK content decreased both RCs absorption and RCs translocation (from root to shoot and from shoot to grain) in buckwheat plants. Since some RCs remains in the soil even after physical decontamination, increasing the soil ExK content is required to decrease the RCs concentration in buckwheat grain, whether or not the field has been decontaminated.…”
Section: Grain Rcs Concentration Affected By Soil Exk Contentsupporting
confidence: 52%
See 1 more Smart Citation
“…A decrease in grain RCs concentration with increasing soil ExK content was also observed in a field that had not been physically decontaminated (soil RCs concentration; <5000 Bq kg −1 ) (Kubo et al, 2015). Kubo et al (2017) demonstrated that higher soil ExK content decreased both RCs absorption and RCs translocation (from root to shoot and from shoot to grain) in buckwheat plants. Since some RCs remains in the soil even after physical decontamination, increasing the soil ExK content is required to decrease the RCs concentration in buckwheat grain, whether or not the field has been decontaminated.…”
Section: Grain Rcs Concentration Affected By Soil Exk Contentsupporting
confidence: 52%
“…Previously, we have shown that the RCs concentration in buckwheat grain can be decreased by increasing the soil exchangeable potassium (ExK) content in RCs-contaminated fields which were not conducted the physical decontamination (Kubo et al, 2015). Recently, Kubo et al (2017) have also reported that increased soil ExK content affects to decreased RCs absorption due to the decreased soil exchangeable RCs concentration and to decreased RCs translocation from root to shoot and from shoot to grain. In addition, Saito and Sato (2014) have reported that the application of cattle manure is useful to increase the soil ExK content and to decrease the RCs concentration in cabbage.…”
Section: Introductionmentioning
confidence: 99%
“…The field conducted our study was loamy clay texture, and the TF values were similar to those previously reported for clay and loam. As the factor affecting to RC transfer from soil to plant, soil exchangeable (plant-available) RCs concentration has had significant positive correlation with RCs concentration in buckwheat cultivated in the field in Fukushima prefecture 16 . Exchangeable RCs in soil can be adsorbed to the frayed edge sites of clay minerals [32][33][34] , and RCs adsorbed to clay minerals becomes difficult to be absorbed by roots of plant.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of increasing potassium (K) applications to decrease RCs transfer from soil to grain, wheat samples that exceed the standard have not been detected since 2012. Increasing K applications has resulted in decreased RCs transfers from the soil to the plants of various species, such as rice (Oryza sativa L.) 12,13 , soybean (Glycine max L.) 14 , buckwheat (Fagopyrum esculentum Moench) [15][16][17][18] and cypress (Chamaecyparis obtusa (Sieb. et Zucc.)…”
mentioning
confidence: 99%
“…Plants were separated into parts (brown rice, husk, and straw), dried for 48 h at 80˚C in an oven, weighed, and ground using a mill for husk and straw. Then, 0.5 g of material was digested in 5.0 mL of HNO 3 for 1 h at 100˚C using a hot block acid digestion system (DigiPREP LS; SCP Science, Quebec, Canada) according to the methods of Kubo et al [31]. The K concentration was determined by an atomic absorption spectrophotometer (ZA3000; Hitachi High-Tech Science Co., Tokyo, Japan).…”
Section: Sampling and K Analysismentioning
confidence: 99%